Transforming professional identity of medical teachers in Pakistan by a certificate program in health professions education: a thematic analysis of reflective essays - Kiran, Faiza; Ayub, Rukhsana; Rauf, Ayesha; Zahoor, Asiya (Frontiers in Medicine, 2024)
Introduction A teacher’s professional identity development is a dynamic and continuous process that requires rigorous, longitudinal, faculty development initiatives which are designed to work on individual professional growth. Impact of such programs must be evaluated by qualitative means to identify the process of change; The purpose of our study was to investigate whether and how our thoughtfully designed 6-month certificate program has transformed the professional identity of medical teachers. Methods The study was conducted in National University of Medical Sciences, Pakistan using thematic analysis, wherein a weekly task of guided reflective writing, on Moodle, was given. Data was analyzed in six phases to achieve credibility and transferability. Results By analyzing 202 reflective writings, seven subthemes were identified which manifest transformation in certain aspects of identity of participants and grouped under three major themes. The seven subthemes represent transformative journey of participants and include recognizing millennial learners’ dilemma, identifying learning gaps and overcoming barriers, discovering a newer version of self, alternative frame of thinking, transforming traditional classroom, conducive learning environment and Community of Practice. Three major themes identified were Awareness, Modeling and Socialization which represent three processes bringing transformation in participants. Conclusion Our faculty development program has transformed certain aspects of professional identities of medical teachers by incorporating informal teaching strategies of experiential learning, professional socialization, reflections, and role modeling. Participants’ beliefs and practices on teaching were challenged by giving a disorienting dilemma of millennial learners and learning theories. They underwent critical discourse with professional peers and mentors in community of practice, reflected on their traditional teaching practices, acquired new insight, underwent self-discovery, and introduced digitalization and interactive learning strategies within their classrooms.